The Effect of using the Smartphone in the Workplace on Job Engagement and Job Burnout: Investigation of Mediational Role of Stress - Somayeh Naghdi Zarrin; Neda Mohammad Esmaeili (مدیریت دولتی)
Objective In today's rapidly evolving digital era, the prevalence of smartphone usage among individuals in various contexts, including both social and professional environments, is witnessing a remarkable increase. This trend is particularly noteworthy in workplace settings, where smartphones have become universal tools offering numerous significant advantages. These benefits range from improved communication and accessibility to vital information to enhanced productivity and collaborative opportunities. However, alongside these advantages, the use of smartphones in professional contexts is also associated with a range of potential drawbacks. These disadvantages can manifest in forms such as distractions, disruptions in work-life balance, and potential breaches of workplace confidentiality. A thorough review of literature focusing on the effects of smartphone use in work environments, particularly in Iran, has identified a notable research gap. Accordingly, this study aims to address this gap by comprehensively describing the effects of smartphone use in the workplace. Additionally, it seeks to propose viable solutions aimed at reducing the excessive use of smartphones in professional settings. Methods This applied research adopts a positivist philosophy and a comparative approach. It is a descriptive, survey-type study using a unique quantitative method. The research examines the status of variables and their interrelationships, utilizing an online questionnaire for data collection. The study's statistical population included 1700 employees from the First Companion Company, with 313 responding to the online questionnaire. Data analysis was performed using SPSS 27 and Smart PLS 3 software. Results The overarching importance of technology in modern life, particularly the role of smartphones, is undeniably significant. The advantages of smartphone use are multifaceted, prominently including their role in facilitating communication and enhancing understanding of work-related tasks. Employees find smartphones indispensable for their daily work interactions and responsibilities. However, the challenge of maintaining a psychological separation from work and phone use is significant. This challenge often leads to a pervasive feeling of constant connection and escalating work pressure, which can adversely affect employees' work-life balance. The resultant anxiety and stress can be substantial, adversely affecting various aspects of work life. This includes detrimental effects on work attitudes, such as job attachment and the onset of job burnout. The findings of this study clearly indicate a positive correlation between the use of smartphones in the workplace and the increase in stress and job burnout. Additionally, the study explores how stress consequent to smartphone use impacts job relationships and contributes to job burnout. Conclusion The research findings indicate that the indirect effect of smartphone usage on job attachment, mediated by stress, is negatively significant. Conversely, the impact of smartphone usage on job burnout, with stress as a mediating factor, is observed to be positive. These results suggest that the use of smartphones, considering stress as a mediating variable, can lead to a reduction in job attachment among employees. Conversely, it can also contribute to an increase in job burnout. Lastly, the study concludes that smartphone use in the workplace positively influences job burnout, while its effect on job attachment is not significant.